IMPACT ON THE IMPLEMENTATION OF MOTHER-TONGUE IN A MULTILINGUAL CLASSROOM - Makena, Bulelwa; Mnyazi-Cweba, Vuyokazi (Universitas Islam Sumatera Utara (UISU), 2024)
Mother-tongue instruction in multilingual settings significantly impacts teaching and learning. This paper aims to investigate the role of teachers in implementing mother-tongue instruction in multilingual classrooms. A qualitative approach was employed for this inquiry, utilizing semi-structured interviews as the primary data collection tool. These interviews featured open-ended questions, allowing participants to respond in detail until data saturation was achieved. Participants were purposively selected and included teachers who provided instruction in the mother tongue, as mandated by policy for Foundation Phase teaching in multilingual education (MLE) settings. The study was conducted in schools within the Eastern Cape Province of South Africa. The findings reveal challenges faced by teachers in implementing and improving mother-tongue instructional materials. Due to a lack of teaching and learning resources, the study concludes that there is a need for libraries in schools. Additionally, the study recommends a thorough examination of innovative teaching strategies.